2020
DOI: 10.1101/2020.11.23.393868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving water quality does not guarantee fish health: effects of ammonia pollution on the behaviour of wild-caught pre-exposed fish

Abstract: Ammonia is a pollutant frequently found in aquatic ecosystems. In fish, ammonia can cause physical damage, alter its behaviour and even cause death. Exposure to ammonia also increases fish physiological stress, which can be measured through biomarkers. In this study, we analysed the effect of sublethal ammonia concentrations on the behaviour and the oxidative stress of Barbus meridionalis that had been pre-exposed to this compound in the wild. Wild-caught fish from a polluted site (pre-exposed fish) and from a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…In fish, ammonia can cause physical damage, alter its behavior such as lower swimming activity and feeding behavior, and oxidative stress response, and even cause death. Exposure to ammonia also increases fish physiological stress and recent evidence suggested that once exposed, fish suffer from reduced antioxidant defenses and thus increased oxidative tissue damage even if water quality was improved [32].…”
Section: Discussionmentioning
confidence: 99%
“…In fish, ammonia can cause physical damage, alter its behavior such as lower swimming activity and feeding behavior, and oxidative stress response, and even cause death. Exposure to ammonia also increases fish physiological stress and recent evidence suggested that once exposed, fish suffer from reduced antioxidant defenses and thus increased oxidative tissue damage even if water quality was improved [32].…”
Section: Discussionmentioning
confidence: 99%
“…During the experimental period, water quality measurements as well as growth metrics were measured on a monthly basis as well. Environmental parameters play an important part in maintaining a healthy habitat for fish to live in, whereas the growth, feed efficiency, and feed intake of fish are typically controlled by a small number of environmental variables in most cases (Komal et al, 2021;Soler et al, 2021;Stavrescu-Bedivan et al, 2016). It also plays a significant role in producing live food organism which is preferred by most of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…98 Wild-caught fish Barbus meridionalis from a polluted site (pre-exposed to ammonia in the wild) exposed to ≥1 mg/L TAN had altered swimming activity (swam less) and feeding behaviour (lower voracity and satiety). 99…”
Section: Behavioural Responsesmentioning
confidence: 99%
“…It should be noted that pre-exposed fish were more sensitive to ammonia exposure than fish from an unpolluted site. 99 The juvenile yellow catfish P. fulvidraco was injected intraperitoneally with ammonium acetate LC50 dose (8 μmol ammonium acetate/g fish). After 7 days, this induced oxidative stress (SOD and CAT activities declined, up-regulation of antioxidant enzymes [Cu/Zn-SOD, CAT, GPx and GR genes transcription]) and apoptosis (up-regulation of p53, Bax, caspase 3 and caspase 9 genes transcription).…”
Section: Oxidative Stress and Apoptosismentioning
confidence: 99%